The advances in the regulation of immune microenvironment by Candida albicans and macrophage cross-talk - Zhao, Shuo; Shang, Anquan; Guo, Mengchen; Shen, Liangliang; Han, Yu; Huang, Xin (Frontiers in Microbiology, 2022)
Candida albicans (C. albicans) is the most common causative agent of invasive fungal infections in hospitals. The body defends against and eliminates C. albicans infection by various mechanisms of immune response, and the latter mechanism of immune evasion is a major challenge in the clinical management of C. albicans infection. The role of macrophages in combating C. albicans infection has only recently been recognized, but the mechanisms remain to be elucidated. This review focuses on the interaction between C. albicans and macrophages (macrophages), which causes the body to generate an immune response or C. albicans immune escape, and then regulates the body's immune microenvironment, to explore the effect of C. albicans virulence resistance versus macrophage killing and clarify the role and mechanism of C. albicans pathogenesis. In general, a thorough understanding of the molecular principles driving antifungal drug resistance is essential for the development of innovative treatments that can counteract both existing and emerging fungal threats.